Carbon isotope ratio mass spectrometry for detection of endogenous steroid use: A testing strategy. Issue 7 (10th January 2013) - Ahrens, Brian D.; Butch, Anthony W.
<x xml:space="preserve">Abstract</x> Isotope ratio mass spectrometry (IRMS) testing is performed to determine if an atypical steroid profile is due to administration of an endogenous steroid. Androsterone (Andro) and etiocholanolone (Etio), and/or the androstanediols (5α‐ and 5β‐androstane‐3α, 17β‐diol) are typically analyzed by IRMS to determine the 13C/12C ratio. The ratios of these target compounds are compared to the 13C/12C ratio of an endogenous reference compound (ERC) such as 5β‐pregnane‐3α, 20α‐diol (Pdiol). Concentrations of Andro and Etio are high so 13C/12C ratios can easily be measured in most urine samples. Despite the potentially improved sensitivity of the androstanediols for detecting the use of some testosterone formulations, additional processing steps are often required that increase labour costs and turnaround times. Since this can be problematic when performing large numbers of IRMS measurements, we established thresholds for Andro and Etio that can be used to determine the need for additional androstanediol testing. Using these criteria, 105 out of 2639 urine samples exceeded the Andro and/or Etio thresholds, with 52 of these samples being positive based on Andro and Etio IRMS testing alone. The remaining 53 urine samples had androstanediol IRMS testing performed and 3 samples were positive based on the androstanediol results. A similar strategy was used to establish a threshold for Pdiol to identify athletes with relatively 13C‐depleted values so that an alternative ERC can be used to confirm or establish a true endogenous reference value. Adoption of a similar strategy by other laboratories can significantly reduce IRMS sample processing and analysis times, thereby increasing testing capacity. Copyright © 2013 John Wiley & Sons, Ltd.